Determinan Pengetahuan Orang Tua, Status Gizi Ibu dan Pola Asuh Balita pada Rumah Tangga Terhadap Probabilitas Stunting di Kota Payakumbuh - Yeni, Vitra; Ariyanto, Edi (Indo-MathEdu Intellectuals Journal, 2025)
This study aims to determine the effect of parental knowledge, maternal nutritional status, and toddler care patterns on the incidence of stunting in Payakumbuh City. The study uses a quantitative approach with a field study design. The sample consisted of 373 respondents, and the data were analysed using logistic regression. The results showed that parental knowledge had a significant effect on the incidence of stunting. Parents with a good understanding of nutrition, balanced diets, sanitation, and child health care tend to be able to apply parenting practices that support toddler growth and development. Maternal nutritional status did not show a significant effect on stunting. Meanwhile, toddler parenting practices were found to have a very significant effect. Feeding practices, developmental stimulation, hygiene, and health care play an important role in preventing stunting.